1996
DOI: 10.1111/j.2042-7158.1996.tb05927.x
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Effects of Unsei-in and Oren-gedoku-to, Chinese Traditional Medicines, Against Rat Paw Oedema and Abdominal Constriction in Mice

Abstract: Oren-gedoku-to and Unsei-in are complex mixtures of ingredients derived from plants. These two drugs are clinically most frequently used in the treatment of Behçet's disease, we have investigated the anti-inflammatory and analgesic actions of Oren-gedoku-to and Unsei-in using a battery of tests; rat paw oedema induced by five different agents; abdominal constriction; mouse ear swelling; and dye leakage tests, designed to clarify the therapeutic potential of these medicines. The findings in this study that thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 15 publications
1
18
0
1
Order By: Relevance
“…In the present experiments, we reconfirmed the effectiveness of repeated administration of Unsei-in at a dose of 300 mg / kg and found that the lower dose of 100 mg / kg was without effect. The effective dose is similar to those in other experiments using mice, such as carrageenan-induced edema (10) and acetic acidinduced abnormal constriction (11). The clinical dose of Unsei-in is 2,400 mg per day.…”
supporting
confidence: 57%
“…In the present experiments, we reconfirmed the effectiveness of repeated administration of Unsei-in at a dose of 300 mg / kg and found that the lower dose of 100 mg / kg was without effect. The effective dose is similar to those in other experiments using mice, such as carrageenan-induced edema (10) and acetic acidinduced abnormal constriction (11). The clinical dose of Unsei-in is 2,400 mg per day.…”
supporting
confidence: 57%
“…Moreover, we have used the carrageenan-induced paw oedema as an in vivo model of inflammation (Winter et al, 1963) because it is a screening procedure in which the involvement of the cyclooxygenase products of arachidonic acid metabolism and the production of reactive oxygen species are well established (Smith et al, 1974). It is reported that the carrageenan oedema shows three distinct phases, namely an initial release of histamine and 5-hydroxytryptamine, a second phase mediated by kinins and a third phase (about 5 h of oedema) in which the mediator is suspected to be prostaglandin (Wang and Mineshita, 1996). Vimang, dependently of dose, inhibited the carrageenan paw oedema in a similar manner to indomethacin in rats at 5 h. Meanwhile, at 3 h the effect of Vimang on hind paw oedema in the guinea-pigs was comparable to naproxen.…”
Section: Discussionmentioning
confidence: 99%
“…47) OGT influences microcirculatory blood flow, which is one of the mechanisms responsible for the efficacy of OGT. 48) Finally, there are many reports that OGT has anti-inflammatory effects, [49][50][51][52] such as the ability to inhibit rat paw oedema. Efforts to identify the active ingredients of OGT and the properties of each ingredient are now under way.…”
Section: Fig 10 Localization Of Cox-2 Expressing Cellsmentioning
confidence: 99%